The Effect of Inventory Management on Company Value (Empirical Study on Food and Beverage Sub-Sector Companies Listed on the Indonesia Effek Exchange in 2020-2023) - Devi Fuspanita; Hakiman Thamrin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to test and analyze the influence of